2020
DOI: 10.1186/s40543-020-00214-w
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent selected reaction monitoring-based GC-MS/MS method for estimation of genotoxic impurities in new antibacterial agent: alalevonadifloxacin mesylate

Abstract: Alalevonadifloxacin mesylate (ALA), pro-drug of levonadifloxacin is a new antibiotic approved in India to treat infections caused by Gram-positive bacteria. Alkyl mesylates (AMs) are known genotoxic impurities (GTI's) formed in drug substances isolated as mesylate salts. Time-dependent selected reaction monitoring (t-SRM)-based gas chromatography tandem mass spectrometry (GC-MS/MS) method has been developed for trace estimation of AMs, namely, methyl methane sulfonate (MMS), ethyl methane sulfonate (EMS) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Ahirrao et al reported a GC-MS method for the estimation of GIs in a new antibacterial agent using selective reaction monitoring (SRM) tool instead of SIM. Mass spectrometer scans all SRM simultaneously they have stated that simultaneous scanning of multiple transition cause lowering of sensitivity but using SRM mode made the method more specific and selective compared to SIM mode [46]. Anerao et al reported that if a large volume of a test sample is introduced into the GC column it can get damage in the long run so to overcome this problem headspace injector is preferred.…”
Section: Challenges In Gc-ms Analysismentioning
confidence: 99%
“…Ahirrao et al reported a GC-MS method for the estimation of GIs in a new antibacterial agent using selective reaction monitoring (SRM) tool instead of SIM. Mass spectrometer scans all SRM simultaneously they have stated that simultaneous scanning of multiple transition cause lowering of sensitivity but using SRM mode made the method more specific and selective compared to SIM mode [46]. Anerao et al reported that if a large volume of a test sample is introduced into the GC column it can get damage in the long run so to overcome this problem headspace injector is preferred.…”
Section: Challenges In Gc-ms Analysismentioning
confidence: 99%
“…Specifically, to detect the methyl methanesulfonate (MMS), ethyl methanesulfonate (EMS), and methyl isopropylsulfonates in Active pharmaceutical ingredient (API) and/or formulated products, the GC-MS methods are effective (Ramakrishna et al, 2008;Wollein and Schramek, 2012;Zhang et al, 2016), whereas using either a simple LC-MS or tandem mass spectrometry (LC-MS/MS) mesylates in benzenesulfonate and/or in p-toluenesulfonates were detected (Kakadiya et al, 2011;Taylor et al, 2006). In addition, a headspace GC-MS in-situ derivatization method for the concurrent measurement of methyl, ethyl, and isopropyl esters of methane/benzene/p-toluenesulfonates, and other sulfates in drug substances was successful (Ahirrao et al, 2020;Alzaga et al, 2007), but already a nonderivatization method was reported for the abovementioned sulfonates by LC-Atmospheric pressure chemical ionization (APCI)-MS/MS (Jin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We are writing to raise serious concerns over about the misleading citation of references in the above article by Ahirrao et al, Journal of Analytical Science and Technology volume 11, Article number: 22 (2020) (Ahirrao et al 2020).…”
Section: Introductionmentioning
confidence: 99%